Designing a Web-Based E-Commerce Application "Sentra Warga" for UMKM - Sari, Nadya Permata; Budiraharjo, Eko (Journal of Social Science and Education Research, 2024)
This research aims to design and implement User Interface (UI) and User Experience (UX) in online store applications intended for Micro, Small, and Medium Enterprises (UMKM). The methods used include analyzing user needs, making initial designs, testing with users, and making improvements based on the feedback received. The user needs analysis stage involves interviews and surveys to understand the preferences and difficulties experienced by UMKM. Initial design creation is carried out with intuitive and easy-to-understand design principles in mind. Testing with users is carried out to evaluate the effectiveness of the design, which is then adjusted based on the feedback obtained. The results of the study show that good UI and UX design can improve user satisfaction, make navigation easier, and speed up the transaction process. In addition, the study highlights that a user-friendly interface can reduce learning time for new users and reduce the error rate in using the application. The importance of the results of this research is to provide an effective and efficient solution for UMKM to increase their competitiveness in the digital market through an easy-to-use online store application. Thus, UMKM can more easily reach potential customers and increase their sales significantly.